TORAKOCHIRRURGIANSCLC: Lung resection in the pulmonary compromised patient - Kowalewski, Janusz; Dancewicz, Maciej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Pulmonary resection remains the only curative treatment option for lung cancer patients. However, only 15-25% of patients with lung cancer are operable because of the extent of the disease and poor cardiopulmonary function. It is essential to select the patients properly for surgery and provide treatment with low postoperative mortality and morbidity. This article discusses the preoperative pulmonary assessment for patient selection (lung volumes, flow rates, diffusing capacity, predicted postoperative pulmonary functions and exercise testing). The preparation of high-risk patients for pulmonary resection is taken into consideration as well (cessation of smoking, bronchodilator drugs, antibiotics, professional rehabilitation). In addition, the options of limited resection are presented (sleeve lobectomy, wedge excision or segmentectomy) as well as a less invasive approach (VATS) and lung volume reduction surgery in this group of patients. The authors emphasise the necessity of close cooperation among a thoracic surgeon, anaesthetist and oncologist to offer potentially curative therapy to these patients.